The Existence of Papaya ringspot virus-Papaya Strain on Cucumber in Gianyar, Bali - Dewa Gede Wiryangga Selangga; I Ketut Widnyana; Listihani Listihani (Jurnal Perlindungan Tanaman Indonesia, 2021)
Yellow mosaic symptoms were identified from cucumber production systems in Gianyar and were similar to symptoms of PRSV infection. Further research was conducted to determine diseases incidence and molecular characteristic of PRSV. Ninety leaf samples were collected from Gianyar by purposive sampling and disease incidence calculations were based on symptoms in the field. Detection and identification were done using a RT-PCR with specific primers of CP PRSV-P, CP PRSV-W and DNA sequencing. Disease incidences in the fields ranged between 5.81–66.87%. Specific DNA band 470 bp was successfully amplified from several cucumber leaf samples collected from Ubud, Payangan, Tegallalang, Sukawati, Gianyar, and Blahbatuh; but no DNA were amplified from all samples when using CP PRSV-W specific primer. Nucleotide and amino acid analysis showed nucleotides homology to isolates from Ubud, Payangan, Tegallalang, Sukawati, Gianyar, and Blahbatuh, i.e. 98.9–99.5% and 99.1–100%, respectively. Results indicated that genetic variation of PRSV-P from Gianyar was low. Furthermore, the nucleotides homology of PRSV-P isolates from Ubud, Payangan, Tegallalang, Sukawati, Gianyar, and Blahbatuh were with PRSV-P isolates which infected cucumbers from Nganjuk (LC311783) and Brebes (LC311784), while from native papaya collected in Bali Bali (LC223115) were 97.2–98.4% and 98.6–100%, respectively. Phylogenetic analysis confirmed that PRSV-P isolates from Indonesia were in the same cluster with Thailand isolates. The results showed that sources of PRSV-P inoculums spreading into new areas.